Philosophical Content in Small Lyrical forms of Sirojiddin Sayyid (On the example of S.Sayyid's collection of poems "Kungil sokhili") - Guljahan Doshanova (Genius Journals, 2023)
This article analyzes the lyrical poems of Sirajaddin Sayid, the peculiarities of his philosophical thoughts in his quatrains.
Keywords: artistic research; small genres; quatrain